2016
DOI: 10.3389/fcell.2016.00078
|View full text |Cite
|
Sign up to set email alerts
|

A New Method to Stabilize C-Kit Expression in Reparative Cardiac Mesenchymal Cells

Abstract: Cell therapy improves cardiac function. Few cells have been investigated more extensively or consistently shown to be more effective than c-kit sorted cells; however, c-kit expression is easily lost during passage. Here, our primary goal was to develop an improved method to isolate c-kitpos cells and maintain c-kit expression after passaging. Cardiac mesenchymal cells (CMCs) from wild-type mice were selected by polystyrene adherence properties. CMCs adhering within the first hours are referred to as rapidly ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
45
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 31 publications
1
45
1
Order By: Relevance
“…As is the case for virtually all other cell types, the vast majority of transplanted c-kit POS CPCs disappeared soon after transplantation (912,14,17). Interestingly, several studies suggested that c-kit POS CPCs possess mesenchymal stromal characteristics and express classic mesenchymal stromal markers, including CD90, CD105, CD29, and CD73 (13,1822), intimating that c-kit POS CPCs might, in fact, be a subset of mesenchymal stromal cells. If this is the case, their reparative actions after MI might relate to the general properties of mesenchymal cells rather than to the expression of c-kit per se.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…As is the case for virtually all other cell types, the vast majority of transplanted c-kit POS CPCs disappeared soon after transplantation (912,14,17). Interestingly, several studies suggested that c-kit POS CPCs possess mesenchymal stromal characteristics and express classic mesenchymal stromal markers, including CD90, CD105, CD29, and CD73 (13,1822), intimating that c-kit POS CPCs might, in fact, be a subset of mesenchymal stromal cells. If this is the case, their reparative actions after MI might relate to the general properties of mesenchymal cells rather than to the expression of c-kit per se.…”
mentioning
confidence: 99%
“…Although c-kit POS CPCs are effective in repairing the infarcted heart, c-kit–based selection is prone to errors and controversy because of variability in c-kit expression levels and reagents (3,13). Furthermore, the expression of c-kit in culture appears to be labile.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It will be also interesting to know the radiation effect specially on the small fraction of c-kit-positive cells in heart2526. However, it is technically difficult for us to get enough number of c-kit-positive cells for experiments because the expression of c-kit is extremely low in the heart tissue of mouse and may loss during ex vivo expansion27. Second, radiation exposure was done at a high dose rate (>12 Gy per hour) in our study.…”
Section: Discussionmentioning
confidence: 99%